Design and implementation of communication protocols for real RFID network - Liu, Shuo (2010)
In RFID applications, collision avoidance for RFID tags is the most important issue to be solved. This report proposes a model for wireless localization system, and an extended tree-splitting algorithm for collision resolution based on existing tree-splitting method. Different from other collision avoidance approaches, which seeks for more efficient random splitting, we reduce the collisions by using the tag mobility characteristic. The existing tags in the system are treated differently from the newly entered tags, and they will communicate with the readers using polling algorithm. Collision avoidance for newly entered tags is based on tree-splitting method. Using this approach, we are able to improve the time efficiency of the whole system. In this report, detailed implementation procedures are shown for protocols applied on both a single-reader system and a further extended reader network. Their performances are also evaluated in terms of time efficiency and information quality.